2020
DOI: 10.3390/biology9020032
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Features of the Anther Development in Tomato Plants with Non-Specific Male Sterility

Abstract: The study was devoted to morphological and cytoembryological analysis of disorders in the anther and pollen development of transgenic tomato plants with a normal and abnormal phenotype, which is characterized by the impaired development of generative organs. Various abnormalities in the structural organization of anthers and microspores were revealed. Such abnormalities in microspores lead to the blocking of asymmetric cell division and, accordingly, the male gametophyte formation. Some of the non-degenerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The aforementioned modifications could alter pollen fitness by reducing the cytoplasmic content and essential materials for exine and intine cell wall production. The literature declared that most of the abnormalities in pollen development are associated with an abnormal tapetal function ( Deng et al, 2018 ; Chaban et al, 2020 ). As expected, diverse factors such as abiotic stresses influence different developmental stages of pollen grain ( Barnabás et al, 2008 ; Smith and Zhao, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned modifications could alter pollen fitness by reducing the cytoplasmic content and essential materials for exine and intine cell wall production. The literature declared that most of the abnormalities in pollen development are associated with an abnormal tapetal function ( Deng et al, 2018 ; Chaban et al, 2020 ). As expected, diverse factors such as abiotic stresses influence different developmental stages of pollen grain ( Barnabás et al, 2008 ; Smith and Zhao, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Any abnormality in anther development may lead to pollen abortion and male sterility ( Qiu et al., 2018 ; Pu et al., 2019 ; Chaban et al., 2020 ; Li et al., 2020 ; Mondol et al., 2020 ; Ren et al., 2020 ; Kim and Kim, 2021 ; Shin et al., 2021 ; Zhang et al., 2021 ; Zheng et al., 2021 ; Deng et al., 2022 ; Qi et al., 2022 ). The male gametophyte in garlic flowers stops at the early stage of sexual cell development ( Koul and Gohil, 1970 ; Tchórzewska et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plants with male sterility cannot produce fertile pollen, and this male sterility may be regulated by genes encoded in the nuclear (genic male sterility) or mitochondrial (cytoplasmic male sterility) genomes ( Garcia et al., 2019 ). Abnormalities in the formation of the pollen sac ( Chaban et al., 2020 ; Zheng et al., 2021 ), meiosis ( Qiu et al., 2018 ; Shin et al., 2021 ), callose ( Pu et al., 2019 ; Li et al., 2020 ), tapetum ( Mondol et al., 2020 ; Zhang et al., 2021 ), pollen wall ( Ren et al., 2020 ; Deng et al., 2022 ), and anther dehiscence ( Kim and Kim, 2021 ; Qi et al., 2022 ) during pollen development can lead to pollen abortion and a male-sterile phenotype. Tapetum and meiocytes are primarily affected in most sporophytic male-sterile mutants ( Guo and Liu, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the sorghum anther developmental process exhibited both similarities and differences with other plant species. We have found that later stages of anther development are much alike across a broad range of different plant species while the early stages vary somewhat among different species (Sanders et al 1999 ; Zhang et al 2011 ; Ekici and Dane 2012 ; Wang et al 2012 ; Xu et al 2014 ; Tsou et al 2015 ; Browne et al 2018 ; Chaban et al 2020 ). The anther development in sorghum resembles mostly to those of maize anthers (Wang et al 2012 ; Moon et al 2013 ; Tsou et al 2015 ), followed by those in wheat and rice (Zhang et al 2011 ; Browne et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%